Police Sexual Misconduct: Arrested Officers and Their Victims - Brewer, Steven L (2014)
Police sexual misconduct encompasses a range of acts from less serious noncriminal behaviors to more egregious criminal behaviors including police sexual violence. Victims of sex crimes are often reluctant to report sexual abuse when the offender is a police officer. The study provides empirical data on 771 sex-related arrest cases in years 2005-2008 of 555 sworn officers at 449 nonfederal law enforcement agencies across the United States. The study identifies and describes incidents where officers were arrested for sex crimes through a quantitative content analysis of published newspaper articles and court records. Findings focus on arrested officers and their victims